Building capacity for the engineering of biology in Australia. Issue 2 (13th June 2021) - Curach, Natalie
Abstract: In Australia, synthetic biology has taken a gradual and rational passage of growth from a collective of discrete practitioners and projects to capacity building initiatives. These initiatives fall under the National Innovation and Science Agenda [2] and have culminated into the formation of hubs of scientific expertise and education supported by the leveraging and enhancement of existing infrastructure networks across the country. The spotlight on science has also motivated more of a whole‐of‐government response to strengthening the nation's entire innovation ecosystem. Policy changes to tax incentives and gene technology regulation have created a momentum which is seeing increasingly more financial backing from Australian and international investors in synthetic biology. With these structures in place, the opportunities afforded by engineering biology have opened for uplifting innovation and the formation of new industries.